2017
DOI: 10.1111/pedi.12527
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and metabolic consequences due to restrictive carbohydrate diets in children with type 1 diabetes: An illustrative case series

Abstract: Low carbohydrate diets for the management of type 1 diabetes have been popularised by social media. The promotion of a low carbohydrate diet in lay media is in contrast to published pediatric diabetes guidelines that endorse a balanced diet from a variety of foods for optimal growth and development in children with type 1 diabetes. This can be a source of conflict in clinical practice. We describe a series of 6 cases where adoption of a low carbohydrate diet in children impacted growth and cardiovascular risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 21 publications
2
65
1
5
Order By: Relevance
“…Dietary patterns that restrict intake from one macronutrient may compromise growth and lead to nutritional deficiencies. 26 National guidelines for adults and children with diabetes in Australia and Canada recommend a carbohydrate intake of at least 45% energy. 2,6 Clinical consensus is that carbohydrate intakes in older, overweight or obese adolescents may be lower (40% energy) with higher protein intakes (25% energy).…”
Section: Energy Intake Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Dietary patterns that restrict intake from one macronutrient may compromise growth and lead to nutritional deficiencies. 26 National guidelines for adults and children with diabetes in Australia and Canada recommend a carbohydrate intake of at least 45% energy. 2,6 Clinical consensus is that carbohydrate intakes in older, overweight or obese adolescents may be lower (40% energy) with higher protein intakes (25% energy).…”
Section: Energy Intake Recommendationsmentioning
confidence: 99%
“…There is international agreement that carbohydrate should not be excessively restricted in children and adolescents with type 1 diabetes as it may result in deleterious effects on growth, a higher cardiovascular risk metabolic profile and increase the risk of disordered eating behaviors. 26 There is evidence from ketogenic diets that low-carbohydrate diets can be nutritionally inadequate and result in growth failure. 32 Restricted carbohydrate diets may increase the risk of hypoglycemia or potentially impair the effect of glucagon in hypoglycemia treatment.…”
Section: Low-carbohydrate Dietsmentioning
confidence: 99%
See 2 more Smart Citations
“…People with Type 1 diabetes on low-carbohydrate diets have low total insulin requirements and unintentional caloric restriction may occur with the adoption of low-carbohydrate diets [24]. A case series described six children with Type 1 diabetes on restrictive carbohydrate diets where growth velocity was decreased [14]. In a recent study, change in height SDS on a low-carbohydrate diet was reported in a subset of 34 children for whom data were available [15].…”
Section: Clinical Considerations Associated With Lowcarbohydrate Dietsmentioning
confidence: 99%